1973
DOI: 10.1128/aac.4.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Tetracycline on the Occurrence of Tetracycline-Resistant Strains of Escherichia coli in the Intestinal Tract of Humans

Abstract: Serial samples of feces from normal human subjects were analyzed for tetracycline-resistant strains of Escherichia coli. Subjects were found to be excreting tetracycline-resistant strains in amounts fluctuating with time. Ingestion of tetracycline increased both the number of individuals excreting tetracycline-resistant strains of E. coli and the proportion of the total E. coli isolates resistant to the antibiotic.Studies show that tetracycline taken orally will increase the number of tetracycline-resistant ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
1

Year Published

1975
1975
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 3 publications
2
8
0
1
Order By: Relevance
“…After treatment with tetracycline (500 mg orally four times a day for 6 days), although there was no significant change in the total numbers of coliforms present more than 50% of these were in each case resistant to tetracycline. This finding agrees with previous similar studies (8,15,18). No V. cholerae were isolated from the post-treatment specimens.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…After treatment with tetracycline (500 mg orally four times a day for 6 days), although there was no significant change in the total numbers of coliforms present more than 50% of these were in each case resistant to tetracycline. This finding agrees with previous similar studies (8,15,18). No V. cholerae were isolated from the post-treatment specimens.…”
Section: Resultssupporting
confidence: 83%
“…In the majority of cases such resistance has been found to be mediated by conjugative R plasmids. Oral administration of antibiotics, particularly tetracycline, may be followed by a marked increase in the numbers of organisms in the bowel flora which are resistant to the administered antibiotic (8,15). In studies by Datta (8), most of these organisms were also found to be resistant to other antibiotics, and again in most cases the resistance was mediated by R plasmids.…”
mentioning
confidence: 99%
“…The relative proportion of resistant strains, however, increased with tetracycline administration and this effect was significantly greater than with doxycycline. Similar changes after oral tetracycline have been previously reported by Hirsh et al (7). These investigators noted that seven of eight subjects shed tetracycline-resistant E. coli during ingestion of this antimicrobial, and that five subjects continued to harbor large populations of resistant strains at least 28 days after therapy was discontinued.…”
Section: Resultssupporting
confidence: 65%
“…2). These factors may explain the reason that when a large number of people are checked once for the bacterial resistance levels in feces, the data obtained display a wide scatter (16,19). The result is that in humans it is almost impossible to detect any minor change in the level of resistance due to the presence of antimicrobial residues.…”
Section: Discussionmentioning
confidence: 96%